“Detection of pathogenic Aeromonas hydrophila from two rainbow trout (Oncorhynchus mykiss) farms in Peru“ - Moya-Salazar, Jeel (2022)
“Fish farms are one of the principal food industries located in peri-urban and rural communities that use available resources to ensure the quality of their products. However, trout can suffer from bacterial infections affecting the sector and being a key component of human health risk. We aimed to identify and characterize Enterobacteriaceae in 46 trout (Oncorhynchus mykiss) in two fish farms in Lima, Peru. Adult trouts older than seven weeks (> 200 grams weight) were included. Cultures were performed in duplicate (n=192 trials) with swabs from the squamous surface and visceral cavity. The isolates were identified with the Vitek® 2 Compact system, and the minimum inhibitory concentrations (MIC) were interpreted with the CLSI VET 03-A guide. At El Molino and El Angelito fish farms, 66 (68.8%) and 57 (59.4%) isolates were obtained. The most frequently isolated species were Escherichia coli (56.8%), Proteus sp. (4.2%) and Klebsiella pneumoniae (2.6%). E. coli was present in all sampling areas, and Aeromonas hydrophila was only present in one open viscera sample at El Angelito fish farm. A. hydrophila showed antibiotic resistance to Ampicillin/Sulbactam (≥32 MIC), Oxytetracycline (>8 MIC), Imipenem (8 MIC), Levofloxacin (>8 MIC), and Ceftazidime (≥64 MIC). Our results suggest the presence of multi-resistant A. hydrophila in O. mykiss. Further studies are needed to understand the developmental context of A. hydrophila, which is crucial to the food industry, aquaculture and public health.“